REABSORÇÃO CONDILAR INTERNA DA ARTICULAÇÃO TEMPOROMANDIBULAR NO PACIENTE ADOLESCENTE - Galiano, Aluísio (2012)
Adolescent internal condylar resorption (AICR) is a progressive disease that affects the temporomandibular joint, which could result in malocclusion, facial deformity, TMJ dysfunction and pain. The onset of this disease occurs between 10 and 15 years, being more common in female adolescents. These patients have characteristic clinical signs such as: increased occlusal and mandibular plane angle, progressive mandibular retrusion, and Class II malocclusion with or without open bite. In imaging studies (computed tomography and magnetic resonance imaging), internal resorption of the condyles and articular disc displacement of the TMJ are observed. Given the difficulty in determining the cause of the AICR and the importance of eliminating pain and improving masticatory function, this study is proposed to evaluate the changes brought to the mandibular positioning and it s long-term stability and the painful symptoms, using the protocol treatment: surgical repositioning of the articular disc and orthognathic surgery performed on the same surgery. In this retrospective study, we assessed the lateral cephalograms obtained at initial assessment (T1), pre-surgery (T2), immediately after surgery (T3), and longest followup, with at least one year post-surgery (T4) and questionnaires of pain and mandibular function of a sample of 24 Class II patients (20 females and 4 males) diagnosed with AICR, wich underwent the treatment protocol: surgical repositioning of the TMJ articular disc simultaneously with orthognathic surgery. The treatment protocol used was fairly positive, since the long-term stability was acquired and a significant improvement in levels of pain and jaw function were achieved. The treatment of patients diagnosed with AICR and treated with the proposed protocol, shows that the procedure is very stable and acts directly on a gain in pain reduction.